Evaluation of clinical outcomes of prophylactic versus preemptive cytomegalovirus strategy in liver transplant recipients. (16th April 2013) - Onor, IfeanyiChukwu O.; Todd, Sarah B.; Meredith, Erika; Perez, Sebastian D.; Mehta, Aneesh K.; Marshall Lyon, G.; Knechtle, Stuart J.; Hanish, Steven I.
Summary Cytomegalovirus (CMV) is a major cause of morbidity and mortality following solid organ transplantation (SOT). Two strategies, prophylactic, and preemptive have emerged for the prevention of CMV infection and disease after SOT. This retrospective chart review of two liver transplant cohorts: prophylactic and preemptive, compares the clinical impact of transitioning from prophylactic to preemptive strategy. The primary outcome is the incidence of CMV viremia at 3‐and 6‐months post‐transplant. Secondary outcomes include: incidence of CMV tissue‐invasive disease, acute cellular rejection, leukopenia and neutropenia, opportunistic infection rates, hospital readmission rates, and mortality at 3‐and 6‐months post‐transplant. A total of 109 patients were included in the analysis. The incidence of CMV viremia was 4.9% and 50.0% (P < 0.001) in the prophylactic versus preemptive cohort, respectively, at 3 months post‐transplant. The incidence of CMV viremia was 24.6% and 8.3% (P = 0.026) in the prophylactic versus preemptive cohort, respectively, at 6 months post‐transplant. There were no statistical significant differences in the secondary outcomes between both cohorts. In conclusion, there is a statistical significant difference in time to onset of CMV viremia; however, the use of either prophylactic or preemptive strategy was not associated with significant negative clinical outcomes of CMV.